Influence Leadership, Competence and Motivation To Performance Employee Service Health Regency Bay Bintuni West Papua Province - Muh Arifai; Abdul Haris; Yasman Yasir; Sudiarti Dewi Kurra; Hardiyanti Hardiyanti; Vivid Violin (Jurnal Ad'ministrare, 2022)
This study aims: (1) to determine the effect of leadership on the performance of the employees of the Teluk Bintuni Regency Health Office, West Papua, (2) to determine the effect of competence on the performance of the employees of the Teluk Bintuni Regency Health Office, West Papua, and (3) to determine the effect of motivation on the performance of the employees of the Teluk Bintuni Regency Health Office, West Papua, and (4) to determine the effect of leadership, competence and motivation on the performance of the employees of the Teluk Bintuni Regency Health Office, West Papua. The variables of this research are leadership as the first independent variable, competence as the second independent variable, motivation as the third independent variable and employee performance as the dependent variable. The population of this study were all civil servants of the Teluk Bintuni Regency Health Office, amounting to 68 people, while the sample of this study was taken with a saturated sample technique so that the sample used was as much as the existing population. Data was collected by using a questionnaire/questionnaire and documentation. Data analysis was performed by descriptive statistical analysis, classical assumption test, instrument test, and hypothesis testing. The results of this study indicate that leadership has a significant effect on employee performance with a significant level <0.05 and competence has a significant effect on employee performance with a significant level <0.05 and motivation has a significant effect on employee performance with a significant level < 0.05. Leadership, competence and work motivation simultaneously have a significant effect on employee performance with a significant level <0.05. In addition, the coefficient of determination (R2) is 0.532 (53.2%). This means that the influence of leadership, competence and motivation on employee performance is 53.2% while the remaining 46.8% is influenced by other factors not examined.